2020
DOI: 10.1111/trf.15911
|View full text |Cite
|
Sign up to set email alerts
|

Differential red blood cell age fractionation and Band 3 phosphorylation distinguish two different subtypes of warm autoimmune hemolytic anemia

Abstract: BACKGROUNDWarm autoimmune hemolytic anemia (wAIHA) is a blood disorder characterized by the increased destruction of autologous red blood cells (RBCs) due to the presence of opsonizing pathogenic autoantibodies. Preliminary reports published more than three decades ago proposed the presence of two wAIHA subtypes: Type I, in which autoantibodies preferentially recognize the oldest, most dense RBCs; and Type II, characterized by autoantibodies that show no preference.STUDY DESIGN AND METHODSWe evaluated patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Those patients showing no difference or even slightly more reactivity with reticulocyte-enriched RBCs, were called Type II and patients as having Type II wAIHA. Other reports have supported these observations [1,19].…”
Section: Warm Autoantibodies Preferencially React With Old Red Blood ...mentioning
confidence: 57%
See 4 more Smart Citations
“…Those patients showing no difference or even slightly more reactivity with reticulocyte-enriched RBCs, were called Type II and patients as having Type II wAIHA. Other reports have supported these observations [1,19].…”
Section: Warm Autoantibodies Preferencially React With Old Red Blood ...mentioning
confidence: 57%
“…Recently, these two specificities of warm autoantibodies were confirmed in 22 patients having wAIHA using discontinuous Percoll gradients to separate reticulocyte-enriched vs. older RBCs [19]. These investigators also showed by Western blot and LC-MS that the warm autoantibodies were reacting with band 3 on the RBCs [19].…”
Section: Key Pointsmentioning
confidence: 83%
See 3 more Smart Citations